Instant Karma The World Anthem Against The Evil By John Lennon: A Psychoanalytic Approach - Yanti, Eka Juni; Soethama, Putu Lirishati; Krisnawati, Ni Luh Putu; Laksminy, Luh Putu (Smart Edu Center, 2023)
This research discusses a concept in which the consequences of one's actions are immediate rather than borne out over a lifetime in Instant Karma! by John Lennon. This descriptive qualitative research focuses to find out how does karma associate with the world anthem against the evil portrayed in John Lennon’s song lyrics Instant Karma!, from the Psychoanalytic theory by Sigmund Freud. The song title is Instant Karma! itself is an implementation of a concept of accountability for your actions. Therefore, the view of the psychoanalytic put forward by Sigmund Freud (1901) is compatible to analyze Instant Karma! by John Lennon. Data were collected by studying, interpreting works of literature, and evaluating them. Studying means getting a better understanding of the song through close readings of the lyrics, contextual insights, and listening to it. Interpreting means trying to find the meaning or theme of the song through related interviews with John Lennon as the writer, composer, and singer. Analyzing through song lyrics was the only way to be done since there was no music video. Evaluating means giving criticism about the song lyrics themselves. Criticism is not all about finding fault or any mistakes, but about how we interpret the meaning of the song itself. The data was collected together one by one through the note-taking approach to discover the data to associate with valid information related. The conclusion shows Instant Karma! by John Lennon portrays the outcome of a person’s actions in past and present states of existence. Those actions lead us to our fate. What comes around, goes around, what we sow, so shall we reap. The Karma itself is not only associated with bad output but also as a good one. Good deeds will have a positive effect while bad deeds will bring negative consequences